2019
DOI: 10.1111/jam.14307
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial succession and co‐occurrence patterns of an enriched marine microbial community during light crude oil degradation in a batch reactor

Abstract: Aims The aim of this study was to investigate the dynamic changes in the bacterial structure and potential interactions of an acclimatized marine microbial community during a light crude oil degradation experiment. Methods and Results The bacterial community effectively removed 76·49% of total petroleum hydrocarbons after 30 days, as evidenced by GC‐FID and GC‐MS analyses. Short‐chain alkanes and specific aromatic compounds were completely degraded within the first 6 days. High‐throughput sequencing of 16S rRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 77 publications
(91 reference statements)
0
9
0
1
Order By: Relevance
“…Natural leaks of oil are widely distributed in the GoM (MacDonald et al, 2015), suggesting that it has a basal level of HDB that can grow to address large-scale oil spills. This hypothesis was validated during the oil spill of the DWH and in later studies, in which metagenomic analysis and isolated cultures showed significant enrichment of bacterial populations related to Oceanospirillum, Cycloclasticus, Colwellia, Pseudoalteromonas, Rhodobacterales, methylotrophs, Alcanivorax, Oleiphilus, Oleispira, Thalassolituus, Oceanospirillales, Marinobacter, Acinetobacter, Pseudomonas and Planomicrobium (Hazen et al, 2010;Kostka et al, 2011;Redmond and Valentine, 2012;Mason et al, 2012;Dubansky et al, 2013;Kimes et al, 2013;Mason et al, 2014;Kleindienst et al, 2015;Orcutt et al, 2017;García-Cruz et al, 2018;Muriel-Millán et al, 2019;Uribe-Flores et al, 2019;Cerqueda-García et al, 2020;Rodríguez-Salazar et al, 2020).…”
Section: Hydrocarbon-degrading Bacteriamentioning
confidence: 66%
“…Natural leaks of oil are widely distributed in the GoM (MacDonald et al, 2015), suggesting that it has a basal level of HDB that can grow to address large-scale oil spills. This hypothesis was validated during the oil spill of the DWH and in later studies, in which metagenomic analysis and isolated cultures showed significant enrichment of bacterial populations related to Oceanospirillum, Cycloclasticus, Colwellia, Pseudoalteromonas, Rhodobacterales, methylotrophs, Alcanivorax, Oleiphilus, Oleispira, Thalassolituus, Oceanospirillales, Marinobacter, Acinetobacter, Pseudomonas and Planomicrobium (Hazen et al, 2010;Kostka et al, 2011;Redmond and Valentine, 2012;Mason et al, 2012;Dubansky et al, 2013;Kimes et al, 2013;Mason et al, 2014;Kleindienst et al, 2015;Orcutt et al, 2017;García-Cruz et al, 2018;Muriel-Millán et al, 2019;Uribe-Flores et al, 2019;Cerqueda-García et al, 2020;Rodríguez-Salazar et al, 2020).…”
Section: Hydrocarbon-degrading Bacteriamentioning
confidence: 66%
“…However, the bacterial community removed 76·49% of total petroleum hydrocarbons after 30 days (Uribe‐Flores et al . ). Santisi et al .…”
Section: Discussionmentioning
confidence: 97%
“…A growing global environmental awareness has prompted an increased interest in the development of more effective technologies for the remediation of contaminated industrial locations and effluents (Uribe-Flores et al 2019). Polycyclic aromatic hydrocarbons (PAH) have attracted attention because of their well-known toxicity, persistence and carcinogenic and mutagenic properties (Di Gregorio et al 2014Ruffini Castiglione et al 2016;Kafouris et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Uribe‐Flores et al (2019) studied the changes in community structure during the degradation of light crude oil by marine microorganisms adapted to the environment by means of multigenomics. The results show that with the degradation of light crude oil, the marine microbial community succession occurs.…”
Section: Application Of Molecular Biology Methods In Pollution Controlmentioning
confidence: 99%